Speaking and Peer Feedback in Lower-Secondary English Classes - Tomášková, Magdalena (Univerzita Pardubice, 2022)
This master thesis deals with speaking and peer feedback in lower-secondary English classes. The theoretical part introduces communicative competence that is more discussed through a construct of Second language speaking competence by Goh and Burns. The second chapter focuses on speaking tasks through which speaking skills can be developed. Finally, it defines feedback generally and then a chapter about peer feedback, its conditions and advantages follow. The practical part consists of action research that focuses on the implementation of peer feedback into English lessons in one selected lower-secondary class.
Mluvní aktivity a vrstevnické hodnocení v hodinách anglického jazyka na druhém stupni základní školy
Keywords: komunikační kompetence; mluvní aktivity; zpětná vazba; vrstevnické hodnocení; implementace vrstevnického hodnocení; communicative competence; speaking tasks; feedback; peer feedback; implementation of peer feedback